Harvesting schedule effects on forage yield and nutritive values in low-lignin alfalfa - Xuan Xu (Journal of Animal Science and Technology, 2022)
Under the four-cut system, low-lignin alfalfa (Medicago sativa L.) may extend harvesting intervals improving harvest management flexibility and producing forage products with higher nutritive values. The objective of this study was to compare forage yield and nutritive values of low-lignin and conventional alfalfa varieties when applied to six different harvest schedules in the first (2016) and second (2017) production years. There were 12 treatments of two alfalfa varieties as whole plots and six harvest schedules as subplots. Across harvest schedules, there were four cuttings in two production years. Three harvest intervals including “Standard” (high quality, HQ), “Standard+5-day” (medium quality, MQ), and “Standard+10-day” (high yield, HY) were chosen for the first cutting, and 30-day (HQ) and 35-day (HY) for the second cuttings. The third and fourth cuttings in 2016 were timed near final harvest date and in 2017 occurred at 35-day (MQ) and 40-day (HY). Variety by harvest schedule interaction was not significant, but the whole plot and sub-plot effects were significant. Hi-Gest 360 was consistently higher in nutritive value and with a similar yield as Gunner. Harvest schedules did not consistently differ in forage yield and nutritive values. HS-1 (“Standard” + 35-day + Medium Quality + High Yield) with shorter first two cutting intervals provided lower acid detergent fiber (ADF), neutral detergent fiber (NDF), higher relative feed value (RFV), and similar forage yield compared to other schedules. HS-1 had the highest economic incomes when considering RFV and yield among the six different harvest schedules.